IMPROVING THE ABILITY OF STUDENTS IN WRITING DESCRIPTIVE TEXT BY USING MIND MAPPING (An Experimental Study at the Second year Students of SMAN 2 Indrajaya) - Jamaliah Jamaliah; Fauziah Fauziah; Cut Indah Putri (Education Enthusiast : Jurnal Pendidikan dan Keguruan, 2021)
The objective of this research was to find out if there is a differences between the students who are tought by using mind mapping technique and the students who are tought by using conventional method to improve the students’ ability in writing descriptive text. The sample of this research were the second year students of SMA 2Indrajaya class XI IPA as experimental class and XI IPS as control class. Each classes consist of 23 students. to collect the data in this quantitative research, the researcher used a set of written test. The reaearcher used an analytic scoring to score the students’ writing both on the pre-test and posttest to attain the reliability of the instrument. The result of students’ pre-test mean score of the experimental class was 58,86 while the students’ post-test mean score was 68,0. The different mean score of t-test is 16,90. The students pre-test mean score in the controlled class was 61,73 and the students post-test mean score was 61,56, and the different mean score with t-test is 8,68. the significant effect was shown by students’ post-test mean score of experimental class which was treated by Mind Mapping Technique, it was greater than the students’ post-test mean score of the controlled class which was not treated by Mind Mapping. This is indicated that the students score in experimental class is better than controlled class. This research can be concluded that the Mind-Mapping technique give better result on students’ writing descriptive text. The Mind Mapping have positive influences and very effective in mastering writing skill especially writing descriptive text.